Analysis of estrogen metabolites in oral Leukoplakia and oral squamous cell carcinoma - GOKUL SRIDHARAN,; PRATIBHA RAMANI,; SANGEETA PATANKAR,; VIJAYARAGHAVAN R, (International Journal of Pharma and Bio Sciences, 2017)
Oral squamous cell carcinoma is an important malignancy of epithelial origin with high rate of morbidity and mortality. While tobacco and alcohol are the primary risk factors; other factors such as microorganisms, chronic irritation and sex hormones along with underlying genetic factors may also contribute to its pathogenesis. The role of sex hormones like estrogen, progesterone and testosterone are known to influence the behavior and prognosis of OSCC. Various estrogen metabolites may possess clinical significance in OSCC and their precursor lesions. The aim of the present study is to assess the regulation of estrogen metabolites in saliva and serum of patients with oral leukoplakia and oral squamous cell carcinoma. Patients diagnosed with oral leukoplakia (n=21) and oral squamous cell carcinoma (n=22) were compared with normal controls (n=18) using QTOF- liquid chromatography mass spectrometry for the detection of estrogen related metabolites in saliva and serum samples. Statistical analysis was performed employing ANOVA, student t-test and Chi-square test to identify the significance of various estrogen metabolites. Salivary estrone-3-glucoronide, estrone-3-sulfate and serum levels of estrone-3-sulfate, estradiol-17β-3-sulfate were significantly upregulated in oral leukoplakia and OSCC than in normal controls while salivary estradiol valerate was significantly downregulated in the diseased groups. The findings suggest the salivary and serum estrogen related metabolites have a significant role in oral leukoplakia and OSCC and could be applicable in cancer therapy.